EFFECTS OF LISTENING ON PUBLIC INSTITUTIONS SERVICE DELIVERY: A CASE STUDY OF KENYA POLICE SERVICE-KISII COUNTY HEADQUARTERS - Keraro, Norah; Muturi, Prof. Willy (Journal of Public Policy and Administration, 2019)
Purpose: To assess the effects of listening on service delivery in Kenya Police Service-Kisii County Headquarters Methods: The study adopted a case study as research design. The study targeted 58 employees who are working in the institution and 152 clients seeking services in the Kenya Police hence the target population was 210. The study sample size comprised of a third of the 42 regular police respondents who included 14 regular police, 1 County Police Commander, 1 Officer Commanding Police Division, 1 Traffic Base Commander, 1 Officer Commanding Station, 4 clerical officers, 3 secretarial staff, 5 support staff and a third of clients seeking service at Kenya Police who were selected by purposive sampling hence 81 respondents were sampled. The researcher utilized both open and closed questionnaires in collection of data. Further descriptive statistics were used in analyzing data. This ensured that the collected data is effectively analyzed in a more organized way to effectively attain the study's objectives. The obtained data would be organized, analyzed and presented through percentages, tables, and frequencies. Results: The study findings indicated that there were effects of listening on service delivery at the Kenya Police Service-Kisii County Headquarters which among them enhanced participation of employees in service delivery, allowing access to relevant information and passing effective information flow. Recommendations: The study recommended that Kenya Police-Kisii County Headquarters should adopt effective communication practices through listening to improve on service delivery in their institution.